Challenges and Future Prospects on 3D in-vitro Modeling of the Neuromuscular Circuit - Badiola-Mateos, Maider; Hervera, Arnau; del Río, José Antonio; Samitier, Josep (Frontiers in Bioengineering and Biotechnology, 2018)
Movement of skeletal-muscle fibres is generated by the coordinated action of several cells taking part within the locomotion circuit (motoneurons, sensory-neurons, Schwann cells, astrocytes, microglia, and muscle-cells). Failures in any part of this circuit could impede or hinder coordinated muscle movement and cause a neuromuscular disease (NMD) or determine its severity. Studying fragments of the circuit cannot provide a comprehensive and complete view of the pathological process. We trace the historic developments of studies focused on in-vitro modelling of the spinal-locomotion circuit and how bioengineered innovative technologies show advantages for an accurate mimicking of physiological conditions of spinal-locomotion circuit. New developments on compartmentalised microfluidic culture systems (cµFCS), the use of human induced pluripotent stem cells (hiPSCs) and 3D cell-cultures are analysed. We finally address limitations of current study models and three main challenges on neuromuscular studies: i) mimic the whole spinal-locomotion circuit including all cell-types involved and the evaluation of independent and interdependent roles of each one; ii) mimic the neurodegenerative response of mature neurons in-vitro as it occurs in-vivo; and iii) develop, tune, implement and combine cµFCS, hiPSC and 3D-culture technologies to ultimately create patient-specific complete, translational and reliable NMD in-vitro model. Overcoming these challenges would significantly facilitate understanding the events taking place in NMDs and accelerate the process of finding new therapies.